Anthropology of the Northern Sea Route: introducing the topic. Issue 1 (2nd January 2017) - Gavrilova, Ksenia; Vakhtin, Nikolai; Vasilyeva, Valeria
Abstract: A new research project Russian Harbors of Transarctic Route: Space and Societies of Russia's Arctic Coast on the Eve of a New Period in the History of Northern Sea Route is briefly outlined in this article. This project, planned for 2017–2019, is an attempt of social science approach to Northern Sea Route from an interdisciplinary, anthropological and historical, perspective. The focus of the project is on different practices of imagining NSR, in the last 100 years as well as today, from both local and broader political perspective. The team will explore the development of the concept of NSR through the lens of historical geography, as well as from social anthropological perspective through research in the coastal communities of the NSR, including ethnographic description of current economic situation, and local infrastructure.